Effect of some weak acids and phytochemicals on malolactic fermentation by Streptococcus mutans - Mai Phuong, Nguyen Thi; Ha, Hoang Phuong; Tra, Pham Thi; Nhung, Tran Thi (Academia Journal of Biology, 2013)
Streptococcus mutans and other certain oral lactic-acid bacteria have demonstrated to possess the ability to carry out malolactic fermentation involving decarboxylation of L-malate to yield L-lactic acid and concomitant reduction in acidity. The activity is inducible by L-malate in S. mutans growing in suspensions or biofilms. Alkalinization is associated with malolactic fermentation resulted in pH rise. Malolactic fermentation (MLF) has been identified as a major system for alkali production by oral streptococci, including S. mutans. Our major objectives in the work described here were to examine the effects of weak acids and some phytochemicals on MLF by S. mutans in both suspension and biofilm states. The obtained data indicated that all week acids tested including triclosan, indomethacin, carpric acid, fluoride and lauric acid inhibited MLF by S. mutans at IC50 of 0.22, 0.25, 0.08, 4.8 và 2.2 mM, respectively. The biofilm cells were also sensitive to the tested agents but at concentration of 10 to 50 folds higher compared to the suspension cells. The inhibition was in a pH dependent manner with increased inhibition was found at lower pH values. For phytochemicals, including a-mangostin and asiatic acid, only a-mangostin showed to be potent for MLF of cells in both suspension and biofilms with IC50 of ca. 45 and > 120 mM, respectively. Asiatic acid had no effect on MLF even at a high concentration of > 50 mM. The net conclusion is that MLF of S. mutans is sensitive to a-mangostin and weak acids, including fluoride and triclosan, which are commonly added to oral care products.